BREAST CANCER, HYPOVITAMINOSIS D AND SLEEP DISTURBANCE AMONG ADULT WOMEN - Zaidi, Syed Muhammad Imran Haider; Yaqoob, Nazia; Bhatti, Khalid Mehmood; Naseem, Madeeha; Javed, Sadaf; Iftekhar, Amina (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine sleep disturbances among adult women with breast cancer and hypovitaminosis D (BCHD). Methodology: A cross sectional self-report predictive study was conducted between March 2017 to July 2017 in Allied Hospital, Faisalabad. Sample was recruited through purposive sampling and consisted of 120 women diagnosed with BCHD. Sleep Disturbance Adult Scale (SDAS), Short Form, translated by researchers in Urdu was used to measure sleep disturbance in patients with BCHD. SPSS version 21 was used for statistical analysis. Results: The mean age of sample was 43.58 ±9.5 years. The hierarchical multiple regression model revealed F= 9.1% of variance in sleep disturbance. Duration of diagnosis and marital status were significant predictors of sleep disturbance (.208 and -.182 respectively), with p <.05. Conclusion: Women with BCHD have mild level of sleep disturbance. Marital status and duration of diagnosis were significant predictors of sleep disturbance in women with BCHD.